Tour Guide’s Safety Culture: First Aid of Wound Injuries in Whitewater Rafting - Ni Putu Ayu Ratih Pinarisraya; Ni Kadek Ayu Suarningsih; I Gusti Ngurah Juniartha (Global Health Science Group, 2021)
Whitewater rafting is a high-risk adventure tourism sport and frequently causes traumatic injuries due to a lack of safety culture implementation. The research aims to know the safety culture in first aid of wound injuries among guide in Ayung River. This was a descriptive study with a quantitative and cross-sectional approach enrolling 140 participants that selected by proportional random sampling technique with inclusion and exclusion criteria. Data was analysed using univariate analysis with frequency distribution. Based on five characteristics of safety culture, the majority of whitewater rafting guide had a good level of value in four categories. Safety culture in whitewater rafting well implemented by guide in Ayung River.